1984
DOI: 10.1038/307641a0
|View full text |Cite
|
Sign up to set email alerts
|

Glial heterogeneity may define the three-dimensional shape of mouse mesencephalic dopaminergic neurones

Abstract: The shape of a neurone--the projection and branching pattern of axons and dendrites--appears to be determined by a combination of intrinisic and environmental influences. We have previously shown that striatal target neurones influence the biochemical maturation of ascending mesencephalic dopamine (DA) cells in culture, as well as the elongation rate of DA neurites. Using a similar approach in which the morphology of individual DA cells can be studied after 3H-DA uptake and autoradiography, we now report on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
151
1
2

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(171 citation statements)
references
References 24 publications
17
151
1
2
Order By: Relevance
“…A variety of coculture experiments (summarized in Table 1) have been performed by several different laboratories, and the results have for the most part been consistent with the hypotheses that homotypic astroglial cells support a greater number of more highly branched dendrites, whereas target-derived astrocytes promote axonal growth (Prochiantz et al, 1990;Rousselet et al, 1990;Qian et al, 1992). For example, Prochiantz and colleagues (Denis-Donini et al, 1984;Chamak et al, 1987;Autillo-Touati et al, 1988;Rousselet et al, 1988Rousselet et al, , 1990Prochiantz et al, 1990) have found that in the embryonic rodent CNS, both mesencephalic and striatal neurons elaborate a greater number of primary neurites when cocultured with astrocytes derived from the homotypic brain region. In addition to the effects on dendrite morphology, Rousselet et al (1990) observed that mesencephalic neurons extended longer axons in media conditioned by striatal (target)-derived astrocytes than by mesencephalon-derived astrocytes.…”
supporting
confidence: 53%
See 2 more Smart Citations
“…A variety of coculture experiments (summarized in Table 1) have been performed by several different laboratories, and the results have for the most part been consistent with the hypotheses that homotypic astroglial cells support a greater number of more highly branched dendrites, whereas target-derived astrocytes promote axonal growth (Prochiantz et al, 1990;Rousselet et al, 1990;Qian et al, 1992). For example, Prochiantz and colleagues (Denis-Donini et al, 1984;Chamak et al, 1987;Autillo-Touati et al, 1988;Rousselet et al, 1988Rousselet et al, , 1990Prochiantz et al, 1990) have found that in the embryonic rodent CNS, both mesencephalic and striatal neurons elaborate a greater number of primary neurites when cocultured with astrocytes derived from the homotypic brain region. In addition to the effects on dendrite morphology, Rousselet et al (1990) observed that mesencephalic neurons extended longer axons in media conditioned by striatal (target)-derived astrocytes than by mesencephalon-derived astrocytes.…”
supporting
confidence: 53%
“…Several lines of evidence suggest that glia from different regions of the CNS differ in their ability to promote neurite outgrowth (Denis-Donini et al, 1984;Chamak et al, 1987;Autillo-Touati et al, 1988;Denis-Donini and Estenoz, 1988;Prochiantz et al, 1990;Qian et al, 1992). Table 1 summarizes these results.…”
Section: Glial Characterizationmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, neurite extension and guidance both require such interactions (Edelman, 1984). Especially pertinent here are the findings of Denis-Donini et al (1984) and Hemmendinger et al (198 l), who have found that extrinsic signals influence the outgrowth of neurites by mesencephalic neurons cultured from normal mice. Abnormal growth signals or abnormal responses to such signals might result in defects in neurite formation in the weaver midbrain, with or without subsequent death of the neurons.…”
Section: Discussionmentioning
confidence: 54%
“…Similar mechanisms are thought to be present in the CNS. The striatum is the major target for dopaminergic neurons originating in the zona compacta ofthe substantia nigra, and some apparently successful attempts have been made to identify the striatal-derived neurotrophic factors that are specific for dopaminergic neurons (Prochiantz et al, 1979, 198 1;Di Porzio et al, 1980;Denis-Donini et al, 1983, 1984. During ontogeny, before the growing axons arrive at their targets, local, glial-mediated neurotrophic support is probably important for survival of dopaminergic neurons (O'Malley et al, 199 1, 1992).…”
Section: Discussionmentioning
confidence: 99%